Edukasi Permainan Balok Susun Guna Mengembangkan Kemampuan Interaksi Sosial Pada Anak - Mardhiah, Ainal; Rahmiati; Isfanda; Hasanah; Winarty, Asih; Hamama, Syarifah Farissi; Samsuar; Cibro, Sania; Sahiran (Yayasan Sagita Akademia Maju, 2024)
Interaction ability and Improvement of a person's personality and character can be encouraged through stimulus with learning strategies that foster children's interest, for example introducing stacking block games in early childhood. Students at Boh Hate Ma Kindergarten are very enthusiastic about stacking block games. Each student cooperated with each other and built communication to choose the appropriate color for the building they were going to shape. The stacking block game is an educational game and is not bound by rules so that students can freely form buildings according to their wishes. The stacking block game is an educational game because it has a positive impact on building interaction for students in Kindergarten Bo hate Ma